2010
DOI: 10.1038/cr.2010.141
|View full text |Cite
|
Sign up to set email alerts
|

Pulse labeling and long-term tracing of newborn neurons in the adult subgranular zone

Abstract: Research over the past decades has demonstrated that adult brain produces neural progenitor cells which proliferate and differentiate to newborn neurons that integrate into the existing circuit. However, detailed differentiation processes and underlying mechanisms of newly generated neurons are largely unknown due to the limitation of available methods for labeling and manipulating neural progenitor cells and newborn neurons. In this study, we designed a tightly controlled, noninvasive system based on Cre/loxP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
46
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 48 publications
3
46
0
Order By: Relevance
“…Importantly, the labeling is permanent once the recombination occurs. By crossing the DCX-CreER mice with reporter mice for inducible expression of yellow fluorescent protein, the authors provided evidence that a majority of labeled neurons are born within a 10 day window before induction [6]. Thus, a cohort of immature neurons with relatively defined birthdates can be selectively pulse-labeled for long-term tracing and for analysis of their morphological and electrophysiological properties in the adult dentate gyrus [6].…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Importantly, the labeling is permanent once the recombination occurs. By crossing the DCX-CreER mice with reporter mice for inducible expression of yellow fluorescent protein, the authors provided evidence that a majority of labeled neurons are born within a 10 day window before induction [6]. Thus, a cohort of immature neurons with relatively defined birthdates can be selectively pulse-labeled for long-term tracing and for analysis of their morphological and electrophysiological properties in the adult dentate gyrus [6].…”
mentioning
confidence: 99%
“…By crossing the DCX-CreER mice with reporter mice for inducible expression of yellow fluorescent protein, the authors provided evidence that a majority of labeled neurons are born within a 10 day window before induction [6]. Thus, a cohort of immature neurons with relatively defined birthdates can be selectively pulse-labeled for long-term tracing and for analysis of their morphological and electrophysiological properties in the adult dentate gyrus [6]. Intriguingly, DCX expressing neuroblasts in the subventricular zone, the largest germinal region in the adult brain which gives rise to newborn interneurons in the olfactory bulb, were not labeled after tamoxifen induction in these mice.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, evidence from adult monkey and human brains suggests that neuroblasts may be generated in the subventricular zone (SVZ) and then continuously migrate to the rostral migratory stream (RMS) [2]. Furthermore, Cheng et al [3] found that newborn neurons in the dentate gyrus (DG) migrated to the inner part of the granule cell layer using a mouse model based on the Cre/loxp system, providing an efficient way to selectively label and manipulate newborn neurons in the adult mouse DG. However, the integration of newborn neurons into the existing circuit is difficult because of their poor survival, insufficient proliferation and differentiation abilities.…”
mentioning
confidence: 99%